Victorians and the prehistoric : tracks to a lost world - Freeman, Michael (Orient Longma, 2004)
"Michael Freeman shows how men and women were both energised and unsettled by the realisation that the formation of the earth over hundreds of millions of years and Darwin's theories about the origins of life contradicted what they had read in the Bible. He describes the rock and fossil collecting craze that emerged, the sources of inspiration and imagery discovered by writers and artists, and the new importance of geologists and paleontologists. He also notes that the intellectual and emotional journey undertaken by Victorian men and women in the face of the unfolding earth narratives was increasingly being recorded, in more institutional form, in the museums that were springing up in Victorian cities and towns."--BOOK JACKET.